Evolutionary Diversification of Alanine Transaminases in Yeast: Catabolic Specialization and Biosynthetic Redundancy - Escalera-Fanjul, Ximena; Campero-Basaldua, Carlos; Colón, Maritrini; González, James; Márquez, Dariel; González, Alicia (Frontiers in Microbiology, 2017)
Gene duplication is one of the major evolutionary mechanisms providing raw material for the generation of genes with new or modified functions. The yeast Saccharomyces cerevisiae originated after an allopolyploidization event, which involved mating between two different ancestral yeast species. ScALT1 and ScALT2 codify proteins with 65% identity, which were proposed to be paralogous alanine transaminases. Further analysis of their physiological role showed that while ScALT1 encodes an alanine transaminase which constitutes the main pathway for alanine biosynthesis and the sole pathway for alanine catabolism, ScAlt2 does not display alanine transaminase activity and is not involved in alanine metabolism. Moreover, phylogenetic studies have suggested that ScALT1 and ScALT2 come from each one of the two parental strains which gave rise to the ancestral hybrid. The present work has been aimed to the understanding of the properties of the ancestral type Lacchancea kluyveri LkALT1 and Kluyveromyces lactis KlALT1, alanine transaminases in order to better understand the ScALT1 and ScALT2 evolutionary history. These ancestral -type species were chosen since they harbor ALT1 genes, which are related to ScALT2. Presented results show that, although LkALT1 and KlALT1 constitute ScALT1 orthologous genes, encoding alanine transaminases, both yeasts display LkAlt1 and KlAlt1 independent alanine transaminase activity and additional unidentified alanine biosynthetic and catabolic pathway(s). Furthermore, phenotypic analysis of null mutants uncovered the fact that KlAlt1 and LkAlt1 have an additional role, not related to alanine metabolism but is necessary to achieve wild type growth rate. Our study shows that the ancestral alanine transaminase function has been retained by the ScALT1 encoded enzyme, which has specialized its catabolic character, while losing the alanine independent role observed in the ancestral type enzymes. The fact that ScAlt2 conserves 64% identity with LkAlt1 and 66% with KlAlt1, suggests that ScAlt2 diversified after the ancestral hybrid was formed. ScALT2 functional diversification resulted in loss of both alanine transaminase activity and the additional alanine-independent LkAlt1 function, since ScALT2 did not complement the Lkalt1Δ phenotype. It can be concluded that LkALT1 and KlLALT1 functional role as alanine transaminases was delegated to ScALT1, while ScALT2 lost this role during diversification.